A comparative study of SiC MOSFETs with and without integrated SBD. (October 2022) - Tang, Lei; Jiang, Huaping; Wei, Jin; Hu, Qiaozhen; Zhong, Xiaohan; Qi, Xiaowei
Abstract: A comparative study on SiC MOSFETs is carried out with an emphasis on the design of integrated Schottky barrier diode (SBD) with numerical simulations by Sentaurus TCAD. Compared with the conventional SiC MOSFET (C-MOS) and the conventional SBD-embedded SiC MOSFET (C-MOSBD), the MOSFET (M-MOSBD) features a hybrid doping mesa above the JFET region where a Schottky contact is formed, which exhibits a superior trade-off between the on-state resistance ( R dson ) and the reverse transfer capacitance ( C rss ). Besides, the integrated diode in M-MOSBD renders a better trade-off between OFF-state junction field ( E Smax ) and forward voltage ( V F ) when compared to C-MOSBD and the conventional junction barrier Schottky diode (JBS), i.e., the external SBD of C-MOS. In the double pulse test simulation, C-MOS exhibited the largest switch loss followed by C-MOSBD, and M-MOSBD is the smallest. Therefore, in power switching applications where reverse conduction is required, M-MOSBD greatly reduces the chip area while presenting better characteristics.